Escraches in feminist university networks: a strategy against gender violence towards women - González, Gema (Universidad de Chile. Instituto de la Comunicación e Imagen, 2019)
This work deals with the topic of Feminism in social networks. It aims to study the development and configuration of 'escrache' as a feminist strategy that helps fighting gender violence against women. In order to do this, this work focuses on the NGO "Red No Estan Solas" (Women are not alone Network), whose Spanish acronym is REDNES. This organization has deployed 'escrache' consistently throughout its existence within the university. REDNES has a particular form of organization and movilization in the digital and physical public space. Therefore, my research relies on a methodology that analyzes the digital data from the fanpage of REDNES. This, along with semi-structured interviews with members of the organization allows me to describe and analyze REDNES ' hybrid collective action.